The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1039/c2dt12337a
|View full text |Cite
|
Sign up to set email alerts
|

3d-Metal derivatives of the [CuI(SO3)4]7− ion: structure and magnetism

Abstract: The Cu(SO(3))(4)(7-) anion, which consists of a tetrahedrally coordinated Cu(I) centre coordinated to four sulfur atoms, is able to act as a multidentate ligand in discrete and infinite supramolecular species. The slow oxidation of an aqueous solution of Na(7)Cu(SO(3))(4) yields a mixed oxidation state, 2D network of composition Na(5){[Cu(II)(H(2)O)][Cu(I)(SO(3))(4)]}·6H(2)O. The addition of Cu(II) and 2,2'-bipyridine to an aqueous Na(7)Cu(SO(3))(4) solution leads to the formation of a pentanuclear complex of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The use of relatively long bridging ligands such as 4,4 0 bipy led to important early examples of the phenomenon of multiple interpenetration in coordination networks. 2,5,6,8,9,12,17,18 Two significant networks reported in these early days were the diamond network, 4,5 in which a tetrahedral metal centre was linked to four crystallographically related centres, and a square grid network (a 4,4 net) in which a square planar or octahedral metal centre (with terminal trans ligands) binds to four bridging 4,4 0 bipy ligands. 2,4,5,12,16 In this current work we report a pair of crystalline networks that share an almost identical arrangement of Cu centres, a feature that appears to allow one crystal to serve as a template for the growth of a topologically distinct second crystal.…”
mentioning
confidence: 99%
“…The use of relatively long bridging ligands such as 4,4 0 bipy led to important early examples of the phenomenon of multiple interpenetration in coordination networks. 2,5,6,8,9,12,17,18 Two significant networks reported in these early days were the diamond network, 4,5 in which a tetrahedral metal centre was linked to four crystallographically related centres, and a square grid network (a 4,4 net) in which a square planar or octahedral metal centre (with terminal trans ligands) binds to four bridging 4,4 0 bipy ligands. 2,4,5,12,16 In this current work we report a pair of crystalline networks that share an almost identical arrangement of Cu centres, a feature that appears to allow one crystal to serve as a template for the growth of a topologically distinct second crystal.…”
mentioning
confidence: 99%
“…Finally, Robson and co‐workers41 reported the synthesis of the 1D Na 3 {[Cu I (SO 3 ) 4 ][Zn II (H 2 O) 2 ] 2 } · H 2 O and Na 3 {[Cu I (SO 3 ) 4 ][Co II (H 2 O) 2 ] 2 } · H 2 O, and 2‐D [Na 4 (H 2 O) 17 ][Ni(H 2 O) 6 ] 2 {[Cu(SO 3 ) 4 ] 2– [Ni(H 2 O) 2 ] 3 } and [Na 4 (H 2 O) 17 ][Co(H 2 O) 6 ] 2 {[Cu(SO 3 ) 4 ] 2 [Co(H 2 O) 2 ] 3 } coordination polymers, demonstrating for the first time the efficacy of the [Cu(SO 3 ) 4 ] 7– anion as a building block for the construction of novel polymeric architectures. Moreover, the same group reported recently42 a family of mixed‐valence Cu I/II /SO 3 2– coordination polymers based on the highly charged [Cu(SO 3 ) 4 ] 7– anion; the authors demonstrated the reactivity of the nucleophilic [Cu(SO 3 ) 4 ] 7– moiety towards first‐row transition metals resulting in finite {[Cu II (H 2 O)(bipy)] 4 [Cu I (SO 3 ) 4 ]}NO 3 · H 2 O, Na 12 {[Cu I (SO 3 ) 4 ] 2 Mn II } · 8H 2 O and Na 3 (H 2 O) 6 [Fe II (H 2 O) 6 ] 2 {[Cu I (SO 3 ) 4 ] 2 [Fe III (H 2 O)] 3 O} · H 2 O, and infinite Na 5 {[Cu II (H 2 O)][Cu I (SO 3 ) 4 ]} · 6H 2 O and (H 2 O) 6 {[Cu I (SO 3 ) 4 ][Mn II (H 2 O) 2 ] 3 } architectures. The reducing environment produced by the sulfite anion promoted the formation of mixed‐valence species in solution as well as the self‐assembly of the generated building blocks into either species with higher nuclearity or infinite coordination polymers.…”
Section: Novel Archetypesmentioning
confidence: 59%
“…The difference in the reaction time for the hydrothermal synthetic procedure (1 day for {Na[Co II 2 (SO 3 ) 2 (μ 3 ‐OH)(H 2 O)]} ∞ and 3 days for {Na 4 [Co II 2 (SO 3 ) 4 ]} ∞ ) allowed control of the materials' ground states ( S T = 0 for {Na[Co II 2 (SO 3 ) 2 (μ 3 ‐OH)(H 2 O)]} ∞ and S T ≠ 0 for {Na 4 [Co II 2 (SO 3 ) 4 ]} ∞ ). In a similar fashion, the mixed‐valence Cu I/II /SO 3 2– family of compounds42 discussed above demonstrate the potential for generating materials in which the controlled assembly of the building blocks (by introduction of structure‐directing ligands) or the availability of specific species (by controlling the ratio/concentration) in solution could modulate the observed magnetic behaviour and “switch” it from ferro‐ to antiferromagnetic. This interesting behaviour demonstrates the efficacy of the sulfite anions in the design of materials that exhibit useful cooperative electronic/magnetic effects, an important requirement for the construction of molecular electronic devices.…”
Section: Materials With Unique Propertiesmentioning
confidence: 84%
“…In fact, only several complexes consisting of 1D aqua-metal chains have been reported 24 where the adjacent metal centers are bridged by two water molecules. Further, infinite aqua-metal species with triple μ 2 -O aqua bridges are even rare and only found for metal ions such as Na I , 25 K I , 26 and Sr II . 27 To our knowledge, complex 3 represents the first example of a [Ca-H 2 O] n chain based on triple aqua bridges.…”
Section: Resultsmentioning
confidence: 99%